PENDAMPINGAN PENGUATAN PENANAMAN NILAI-NILAI PROFETIK DALAM PROSES BELAJAR DAN MENGAJAR BAGI GURU DI PONDOK PESANTREN MATHOLI’UL ANWAR REK-KERREK PALENGAAN - H. Mosleh Habibullah; Achmad Baidawi; Mulyadi Mulyadi; Eva Nikmatul Rabbianty; Wahab Syakhirul Alim (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
One of the goals of education is to produce a generation that has commendable behavior as exemplified by the Prophet Muhammad SAW. This community service activity aims to equip teachers at Pondok Pesantren Matholiul Anwar either theoretical or practical to instill prophetic values ​​in teaching and learning activities in the classroom. This community service activity is carried out by providing counseling which is conducted through presentation from the resource persons and followed by a question and answer or discussion session. From this activity, the teachers seemed enthusiastic in participating and they were very enlightened and helped to further strengthen the practice of instilling prophetic values ​​in teaching and learning activities. This community service activity is expected to improve the quality of a more integrative teaching and learning process.